Eksplorasi Potensi Ekstrak Gambir (Uncaria Gambir Rox.b) dan Daun Pepaya (Carica Papaya L.) sebagai Masker Wajah - Adinda Putri Anggia; Linda Rosalina (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Mask is a facial care cosmetic that functions to cleanse dirt from the face, such as removing dead skin cells, cleaning skin pores, reducing excess oil, and alleviating skin irritation. This study combines gambir and papaya leaves as a mask, aiming to provide comprehensive benefits for the facial skin, including combating aging, addressing acne, and maintaining skin elasticity. Qualitative and descriptive methods were employed in this research to determine the pH, flavonoid, and alkaloid content (laboratory tests). The research began by soaking gambir and papaya leaf powder in 96% ethanol for three days, followed by filtration of the maceration results, yielding extracts 1, 2, and 3, which were then concentrated using a rotary evaporator. The thick extract was then formulated into a peel-off mask according to predetermined formulations. The results of the flavonoid, alkaloid, and pH tests showed concentrations of F1=5.75, F2=5.45, and F3=5.32, with flavonoid tests for F1, F2, and F3 being positive for flavonoids, and alkaloid.